Hubungan Pola Makan dengan Kejadian Obesitas pada Anak di Sekolah Dasar Cikarang Kota Kabupaten Bekasi - Hidayah, Feni; Dandi Sanjaya; Deni Alamsah; Nur Fauzia Asmi (Lembaga Pengembangan Kinerja Dosen, 2026)
Childhood obesity is a global health problem whose prevalence continues to increase, including in Indonesia. An imbalanced diet contributes to the accumulation of body fat. This condition impacts the physical, psychological, and social health of children so it needs to be prevented through healthy eating habits from school age. This study aims to determine the relationship between eating patterns and the incidence of obesity in elementary school children in Cikarang City, Bekasi Regency. This study is quantitative using a cross-sectional design. The sampling technique uses a non-probability sampling method with a purposive sampling approach. Data were obtained by anthropometric measurements, filling out a food frequency questionnaire (FFQ) guided by the researcher. Data analysis was carried out to test the hypothesis using the Chi-Square test using SPSS, the study was conducted at Cikarang City Elementary School, Bekasi Regency in June 2025. The results of the study from a total of 43 children as the study sample, there were 30 children (69.8%) who were obese. In addition, 24 children (55.8) were found to have inadequate eating patterns. The results of the statistical analysis of the relationship between eating patterns and obesity (p-value 0.001). There is a significant relationship between eating patterns and the incidence of obesity in elementary school children in Cikarang City, Bekasi Regency.